If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -10y = -8y Solving 8 + -10y = -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. 8 + -10y + 8y = -8y + 8y Combine like terms: -10y + 8y = -2y 8 + -2y = -8y + 8y Combine like terms: -8y + 8y = 0 8 + -2y = 0 Add '-8' to each side of the equation. 8 + -8 + -2y = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -2y = 0 + -8 -2y = 0 + -8 Combine like terms: 0 + -8 = -8 -2y = -8 Divide each side by '-2'. y = 4 Simplifying y = 4
| b-5+8b=33 | | 226.8=21.7y | | 8m(m-3)=56 | | -80-11x=5x+144 | | 216x+36=15+12x | | 3(r-3)+7r=54 | | y=8-6 | | y+g=12 | | 20y+3y= | | 216=36x+15+12x | | 24=w+8 | | 5x-11+5x=21 | | 5+4w=-8 | | 216+36x=15+12x | | 16y+11y= | | 5n^2+19n-69=-2 | | 24=w+6 | | 3y+1=21 | | -8x-163=101+3x | | -7.2=80x | | 17x=26 | | 8x-13x=26-34 | | 3m-[m+1]=6m+1 | | 42.34=9g+3.82 | | 6x-9=110-11x | | 7x+1=2x-4 | | 5x+2(3x+8)+17=4x+21 | | 5-3(x-7)=2(2-x) | | 2m^3(4m^2)= | | 4(x^3-6x^2+9)=0 | | 500=30f+100 | | x=9x-22 |